Efficiency comparison of digital content providers with different pricing strategies. Issue 2 (May 2017) - Na, Ho Seoung; Hwang, Junseok; Hong, Jasmine Yoo Jung; Lee, Daeho
Highlights: This paper categorizes digital content firms based on the pricing strategy. It compares the efficiency of firms using meta-frontier analysis method. The free group has the highest efficiency, followed by the fee group. Abstract: Unlike traditional products, digital content can be offered free because the marginal cost required for additional production is close to zero. Since free digital content is offered at a lower price than that of the competitors, it is a strategy that can beat the competition. However, digital content firms use various strategies, such as the advertising sales-based strategy, freemium strategy, and membership fee-based strategy. This study categorizes Korea's digital content firms into three groups based on the pricing strategy and uses the meta-frontier analysis method in order to determine which group's production function is closer to the meta-frontier production function. In addition, Tobit regression is used to analyze whether the differences in the efficiency levels between groups are statistically significant. The results reveal that the free group has the highest efficiency, followed by the fee group and the mix group in that order.